THE DEVELOPMENT OF KIT STUDENT WORKSHEET ON ACID BASE TO TRAIN SCIENCE PROCESS SKILL OF 11TH GRADE STUDENT (UNESA Journal of Chemical Education, 2017)
The study was aimed to know feasibility of kit student worksheet on acid base to train science process skill. The feasibility was assessed according theoretically and empirically feasibility. Theoretically feasibility obtained from validation result in content, presenting, language, and graphical criteria. Empirically feasibility obtained from student respond, appropriateness of lesson plan, and science process skill test. This research use 4-D Model of Development but implemented until develop phase. This research was tested to 16 students from XI-MIA 2 SMAN 11 Surabaya for two meetings with indicator and pH of acid base; and neutralization reaction as sub matter. Instruments in this research were validation, student respond, and observation sheet. Result of this research shown that kit Student Worksheet on Acid Base to train science process skill was feasible to use that proven with: 1) Result of theoretically feasibility with percentage range 73.33%-93.33%. (2) Result of empirically feasibility with percentage range of student responses was 81.25%-100.00% and all activities was appropriate with lesson plan. 3) Result of science process skill test was increased its proven by n-gain result for pretest 1-posttest 1 and pretest 2-posttest 2 was on category medium-high and the completeness percentage of science process skill components which on range 48,50%-98,50% in posttest 1 and 72,00%-100,00% in posttest 2. Keywords: kit student worksheet, acid base, science process skill.